2006
DOI: 10.1295/polymj.38.184
|View full text |Cite
|
Sign up to set email alerts
|

Thermal, Structural, and Viscoelastic Characterization of cis-Poly(phenylene vinylene) Related to its Photo-Isomerization

Abstract: ABSTRACT:A cis-poly(phenylene vinylene) (cis-PPV) recently synthesized by Katayama, Ozawa, and coworkers undergoes photo-isomerization into trans configuration. This isomerization occurred rather quickly within 45 min in solvent-cast films at room temperature. The cis-PPV chains exhibiting this quick isomerization were expected to be highly mobile in the bulk state, and this expectation was examined from thermal, structural, and viscoelastic tests for a cis-PPV sample with M n ¼ 4300 and M w =M n ¼ 2:16. It tu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…The charge carrier mobility of polymers with trans -vinylene and thiophene-derived repeating units ( trans -poly­(thienylenevinylene)­s; PTVs) has been reported to be the highest among π-conjugated polymers. However, trans -PTVs have strong interchain π–π interactions due to their planar structure, which limits their solubility. , The more twisted configuration of the cis -vinylene units tends to result in less optimized interchain stacking and thus higher solubility . We have demonstrated that thin films of cis -poly­( p -phenylenevinylene)­s undergo cis-to-trans isomerization under UV irradiation (Figure e). A similar isomerization of cis -vinylene may provide a direct and efficient route to the fabrication of trans -PTVs thin films (Figure f).…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…The charge carrier mobility of polymers with trans -vinylene and thiophene-derived repeating units ( trans -poly­(thienylenevinylene)­s; PTVs) has been reported to be the highest among π-conjugated polymers. However, trans -PTVs have strong interchain π–π interactions due to their planar structure, which limits their solubility. , The more twisted configuration of the cis -vinylene units tends to result in less optimized interchain stacking and thus higher solubility . We have demonstrated that thin films of cis -poly­( p -phenylenevinylene)­s undergo cis-to-trans isomerization under UV irradiation (Figure e). A similar isomerization of cis -vinylene may provide a direct and efficient route to the fabrication of trans -PTVs thin films (Figure f).…”
Section: Introductionmentioning
confidence: 98%
“…Instead, thin films are fabricated from soluble precursor materials and directly converted to the desired compounds via heating and/or light exposure in the solid state. While precursor reactions often form volatile byproducts that may disrupt the film morphology (Figure a–d), isomerization is an ideally “clean” pathway with no chemical byproducts. Our group has previously reported a precursor method using cis-to-trans isomerization of vinylene units integrated into a polymer backbone (Figure e). …”
Section: Introductionmentioning
confidence: 99%